Getting learners to speak in the (Indonesian) ELT classroom - Timmis, Ivor (UPT Bahasa Universitas Tanjungpura, 2019)
Despite realising the importance of acquiring good speaking skill, English teachers in Indonesia find that it is challenging to get their learners to speak during classes. Potential reasons for reticence are: their lack of vocabulary, dependency of L1 translation, and tendency to give short answers. Therefore, it is crucial to provide the teachers with practical techniques that they can use in their daily teaching to address this reticence. By providing scaffolding to the speaking activities, which includes how to structure the speaking activities and prepare the learners before the activities, the teacher can make speaking tasks more productive for learners. Moreover, the amount of scaffolding can be adjusted to suit the characteristics and needs of the learners to create better and lasting impact.